Improved in situ detection method for telomeric tandem repeats in metaphase spreads and interphase nuclei. Issue 1 (1st February 2000) - Uhlmann, V; Prasad, M; Silva, I; Luettich, K; Grande, L; Alonso, L; Thisted, M; Pluzek, K J; Gorst, J; Ring, M; Sweeney, M; Kenny, C; et al.
Abstract : Peptide nucleic acid technology (PNA) has become an extremely useful tool and promises to impact on molecular biology and diagnostics. These synthetic DNA analogues pair with DNA and RNA molecules according to Watson and Crick base pairing rules. This paper describes a sensitive and quick fluorescent in situ hybridisation (ISH) technique to determine DNA telomere repeat sequences (TTA GGG)n using epifluorescence microscopy. Telomeres are special, repeated structures at the end of each eukaryotic chromosome and serve as protective caps to prevent DNA rearrangements and fusion of chromosomes. A model system has been developed, using stimulated peripheral blood lymphocytes, which facilitates simultaneous detection of telomeres in metaphase as well as in interphase nuclei. A fluorescein isothiocyanate labelled PNA probe (18 mer) directed against complementary telomeric sequences at the end of each chromosome is used. In addition, a simple, easy to perform PNA-ISH protocol is described that overcomes common hybridisation problems encountered using DNA and RNA oligoprobes. Furthermore, the usefulness of a chromogenic immunocytochemical detection system is shown for PNA-ISH.